Effects of Strategy Implementation Drivers on the Performance of Tea Processing Factories in Kisii County, Kenya - Kerubo, Ondari Josephine; Koech, Caroline Sitienei; Otieno, Simeyo (AJHSSR, 2020)
Various prior studies have concurred that 90% of strategic initiatives fail, not due to formulation but, due to implementation difficulties. Failure of strategy implementation efforts causes enormous costs in the organization. Despite the importance of the implementation process within strategic management, it is often overshadowed by a focus on the strategy formulation process. The study sought to determine the effect of strategy implementation drivers (leadership, organizational culture, organizational structure and human resource development) on the performance of tea processing factories in Kisii County. The target population of this study was 846 employees of five (5) tea processing factories in Kisii County. Both stratified sampling and simple random sampling were used to obtain a sample of 264 employees from whom primary quantitative data was collected and analyzed using descriptive statistics and multiple linear regression analysis. The correlation analysis results showed a positive correlation between the strategy implementation drivers and the performance of tea factories. Leadership was established to have a positive effect on performance which was however not significant. Organizational culture, structure and human resource development all had a statistically significant positive effect on the performance of tea factories. The standardized beta coefficients indicated that human resource development had the greatest effect size hence the recommendation by the study for tea factories to focus more on improving its human resource development practices as a precursor to improved performance.
Keywords: Strategy Implementation drivers; Performance; Leadership; Organizational culture; Organizational structure; Human resource development